2022
DOI: 10.3390/idr14050075
|View full text |Cite
|
Sign up to set email alerts
|

HIV and Mediterranean Zoonoses: A Review of the Literature

Abstract: A zoonosis is an infectious disease that has jumped from a non-human animal to humans. Some zoonoses are very common in the Mediterranean area and endemic in specific regions, so they represent an important problem for public health. Human Immunodeficiency Virus (HIV) is a virus that has originated as a zoonosis and is now diffused globally, with the most significant numbers of infected people among the infectious diseases. Since the introduction of antiretroviral therapy (ART), the history for people living w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 163 publications
0
2
0
Order By: Relevance
“…Acquired immunodeficiency syndrome (AIDS) is a chronic, potentially life-threatening condition caused by the human immunodeficiency virus (HIV). Interestingly, based on findings demonstrating that HIV developed as a result of multiple cross-species transmissions from simian immunodeficiency virus (SIV), AIDS has been reported to be the most important zoonosis in our recent history, killing more than 25 million people [ 1 , 12 , 13 ]. HIV has probably “jumped” to humans from a West African subspecies of chimpanzee ( Pan troglodytes troglodytes ).…”
Section: Introductionmentioning
confidence: 99%
“…Acquired immunodeficiency syndrome (AIDS) is a chronic, potentially life-threatening condition caused by the human immunodeficiency virus (HIV). Interestingly, based on findings demonstrating that HIV developed as a result of multiple cross-species transmissions from simian immunodeficiency virus (SIV), AIDS has been reported to be the most important zoonosis in our recent history, killing more than 25 million people [ 1 , 12 , 13 ]. HIV has probably “jumped” to humans from a West African subspecies of chimpanzee ( Pan troglodytes troglodytes ).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, no cyst stage information was provided, which weakens their conclusions. In their recent reviews, Russotto et al [24] reported that cystic echinococcosis is a common co-infection in patients with HIV in endemic countries, and Ghasemirad et al [25 ▪ ] specifically highlighted the impossibility, from current literature, to draw conclusions on any possible difference in the clinical course of the infection in immunocompromised compared with immunocompetent patients. No longitudinal studies compared the long-term outcome of patients with cystic echinococcosis and concomitant immunosuppressive conditions, which could provide robust data while avoiding the potential bias due to clinical observation and publication of only symptomatic, severe and complicated cases (Supplementary file 2, http://links.lww.com/COID/A49).…”
Section: Special Conditions: Immunosuppression and Pregnancymentioning
confidence: 99%